A novel polymorphism in the oxytocin receptor encoding gene (OXTR) affects milk fatty acid composition in Italian Mediterranean river buffalo. Issue 2 (19th May 2017) - Cosenza, Gianfranco; Macciotta, Nicolò P P; Nudda, Anna; Coletta, Angelo; Ramunno, Luigi; Pauciullo, Alfredo
Abstract : The oxytocin receptor, also known as OXTR, is a protein which functions as receptor for the hormone and neurotransmitter oxytocin and the complex oxytocin–oxytocin receptor plays an important role in the uterus during calving. A characterisation of the river buffalo OXTR gene, amino acid sequences and phylogenetic analysis is presented. The DNA regions of the OXTR gene spanning exons 1, 2 and 3 of ten Mediterranean river buffalo DNA samples were analysed and 7 single nucleotide polymorphisms were found. We focused on the g.129C > T SNP detected in exon 3 and responsible for the amino acid replacement CGC Arg > TGC Cys in position 353. The relative frequency of T allele was of 0·257. An association study between this detected polymorphism and milk fatty acids composition in Italian Mediterranean river buffalo was carried out. The fatty acid composition traits, fatty acid classes and fat percentage of 306 individual milk samples were determined. Associations between OXTR g.129C > T genotype and milk fatty acids composition were tested using a mixed linear model. The OXTR CC genotype was found significantly associated with higher contents of odd branched-chain fatty acids (OBCFA) ( P < 0·0006), polyunsaturated FA (PUFA n 3 and n 6) ( P < 0·0032 and P < 0·0006, respectively), stearic acid (C18) ( P < 0·02) and lower level of palmitic acid (C16) ( P < 0·02). The results of this study suggest that the OXTR CC animals might be useful in selection toward the improvement of milk fatty acid composition.